Neuroplasticity to autophagy cross-talk in a therapeutic effect of physical exercises and irisin in ADHD - Abdulghani, Alhasan; Poghosyan, Mikayel; Mehren, Aylin; Philipsen, Alexandra; Anderzhanova, Elmira (Frontiers in Molecular Neuroscience, 2023)
Adaptive neuroplasticity is a pivotal mechanism for healthy brain development and maintenance, as well as its restoration in disease- and age-associated decline. Management of mental disorders such as attention deficit hyperactivity disorder (ADHD) needs interventions stimulating adaptive neuroplasticity, beyond conventional psychopharmacological treatments. Physical exercises are proposed for the management of ADHD, and also depression and aging because of evoked brain neuroplasticity. Recent progress in understanding the mechanisms of muscle-brain cross-talk pinpoints the role of the myokine irisin in the mediation of pro-cognitive and antidepressant activity of physical exercises. In this review, we discuss how irisin, which is released in the periphery as well as derived from brain cells, may interact with the mechanisms of cellular autophagy to provide protein recycling and regulation of brain-derived neurotrophic factor (BDNF) signaling via glia-mediated control of BDNF maturation, and, therefore, support neuroplasticity. We propose that the neuroplasticity associated with physical exercises is mediated in part by irisin-triggered autophagy. Since the recent findings give objectives to consider autophagy-stimulating intervention as a prerequisite for successful therapy of psychiatric disorders, irisin appears as a prototypic molecule that can activate autophagy with therapeutic goals.